Outlander : Season one, Volume One, Disc 3 - Gabaldon, Diana (Australia : Universal Sony Pictures Home Entertainment Australia [distributor], 2014)
British combat nurse Claire Randall is reunited with her husband after returning from the battlefields of World War II. While on their second honeymoon, she walks through one of the ancient stone circles that dot the British Isles and is suddenly transported to 1743 Scotland, torn by war and rogue Highland clans. Hurled back in time by forces she cannot understand Clarie is catapulted into intrigue and danger when she is accused of being a spy. Forced by circumstance to marry an outlawed Highlander, she finds herself falling in love and torn by her loyalties to two men in vastly different times, all of which may threaten her life and shatter her heart.
Rated MA 15+ : Strong themes, violence, sexualised violence, sex scenes, sexual references, nudity and coarse language. Based on the Internationals Bestseller. Special features: Gag reel ; Volume One -An epic adaptation ; The dresses & kilts of Outlander. Executive producer, Ronald D. Moore. Sam Heughan, Caitriona Balfe, Tobias Menzies. In English, German. Subtitles in English, Danish, Finnish, German, Hindi, Norwegian, Polish, Swedish, Turkish. English Captions (Descriptive subtitles for the hearing impaired)
Outlander. Season one, volume one (Approximately 458 min.)
Rated: MA15+
109967
Keywords: Nurses -- Great Britain -- Drama; Scotland -- Drama; Time travel -- Drama; Outlaws -- Scotland -- Drama; Man-woman relationships -- Drama